Teacher Competencies in Character Strengthening for Early Childhood - Aisyah, Siti (JURNAL PENDIDIKAN USIA DINI, 2023)
Character education is very basic education for young children to instill moral values to prevent unacceptable behavior. Children can absorb good character if they are in a supportive environment, for this reason, schools should understand and implement character education in the learning process. This research aims to see how teachers apply the character values of responsibility, honesty, discipline, love and affection, caring, courage, independence, hard work, cooperation, courtesy, justice, self-control, and tolerance. This survey method research uses two types of mixed data (Mixed method) with data collection techniques through observations, types of tasks, and performance assessments. The respondents for this research were 49 teachers involving 112 children. The results of research with a regression model of 0.7895 shows that the variables Responsibility, Honesty, Discipline, Caring, Courage, Independence, Hard Work, Cooperation, Politeness, Fairness, Self-Control, and Tolerance can explain the diversity of children's characters by 78.95%. while the rest is explained by other variables outside the model. Character values can be taught optimally in the school environment based on the teacher's ability to implement them. Through character education at school, children can also instill a positive outlook on life. Keywords: Teacher competency, Character Strengthening, Early Childhood References: Adi, H. C., Zulvia, M., & Asyha, A. F. (2020). Studi Kompetensi Guru dan Linieritas Pendidikan dalam Peningkatan Prestasi Belajar Siswa di Sd Negeri 1 Gunung Tiga Dan Sd Negeri 1 Ngarip Lampung. Al-Tadzkiyyah: Jurnal Pendidikan Islam, 10(2), 245–255. https://doi.org/10.24042/atjpi.v10i2.5140 Akdeniz, C. (2016). The relationship between elementary school teachers’ personality types and their learning and instructional strategies. International Journal of Curriculum and Instruction, 41(36). Anggraini, N. (2021). Peranan Orang Tua Dalam Perkembangan Bahasa Anak Usia Dini. Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 7(1), 43. https://doi.org/10.30595/mtf.v7i1.9741 Backman, E., & Barker, D. M. (2020). Re-thinking pedagogical content knowledge for physical education teachers – implications for physical education teacher education. Physical Education and Sport Pedagogy, 25(5), 451–463. https://doi.org/10.1080/17408989.2020.1734554 Canales, A., & Maldonado, L. (2018). Teacher quality and student achievement in Chile: Linking teachers’ contribution and observable characteristics. International Journal of Educational Development, 60, 33–50. https://doi.org/10.1016/j.ijedudev.2017.09.009 Castillo-Gualda, R., Herrero, M., Rodríguez-Carvajal, R., Brackett, M. A., & Fernández-Berrocal, P. (2019). The role of emotional regulation ability, personality, and burnout among Spanish teachers. International Journal of Stress Management, 26(2), 146–158. https://doi.org/10.1037/str0000098 Coyne, I. (2009). Research with Children and Young People: The Issue of Parental (Proxy) Consent. Children & Society, 24, 227–237. Davidson, M., Khmelkov, V., & Lickona, T. (2010). The Power of Character: Needed for, and Developed from, Teaching and Learning. In T. Lovat, R. Toomey, & N. Clement (Eds.), International Research Handbook on Values Education and Student Wellbeing (pp. 427–454). Springer Netherlands. https://doi.org/10.1007/978-90-481-8675-4_26 Fabbro, A., Fabbro, F., Capurso, V., D’Antoni, F., & Crescentini, C. (2020). Effects of Mindfulness Training on School Teachers’ Self-Reported Personality Traits As Well As Stress and Burnout Levels. Perceptual and Motor Skills, 127(3), 515–532. https://doi.org/10.1177/0031512520908708 Flanagan, A. M., Cormier, D. C., & Bulut, O. (2020). Achievement may be rooted in teacher expectations: Examining the differential influences of ethnicity, years of teaching, and classroom behaviour. Social Psychology of Education, 23(6), 1429–1448. https://doi.org/10.1007/s11218-020-09590-y Gordon, H. R. D., & Yocke, R. (1999). Relationship Between Personality Characteristics and Observable Teaching Effectiveness of Selected Beginning Career and Technical Education Teachers. Journal of Career and Technical Education, 16(1). https://doi.org/10.21061/jcte.v16i1.707 Haslip, M. J., Allen-Handy, A., & Donaldson, L. (2020). How urban early childhood educators used positive guidance principles and improved teacher-child relationships: A social-emotional learning intervention study. Early Child Development and Care, 190(7), 971–990. https://doi.org/10.1080/03004430.2018.1507027 Jovanović, J., Gašević, D., Dawson, S., Pardo, A., & Mirriahi, N. (2017). Learning analytics to unveil learning strategies in a flipped classroom. The Internet and Higher Education, 33, 74–85. https://doi.org/10.1016/j.iheduc.2017.02.001 Kim, H., & Sasaki, J. Y. (2017). 26—Intercultural similarities and differences in personality development. In J. Specht (Ed.), Personality Development Across the Lifespan (pp. 419–434). Academic Press. https://doi.org/10.1016/B978-0-12-804674-6.00026-0 Puspitasari, Taufiq Satria Mukti, Supriyanto, & Muhammad Munadi. (2021). Character Building Through the Synergy Between Parents and School in Indonesia. Proceedings of the International Conference on Engineering, Technology and Social Science (ICONETOS 2020), 16–21. https://doi.org/10.2991/assehr.k.210421.003 Rokhman, F., Hum, M., Syaifudin, A., & Yuliati. (2014). Character Education for Golden Generation 2045 (National Character Building for Indonesian Golden Years). Procedia - Social and Behavioral Sciences, 141, 1161–1165. Roth, V., & Christine, A.-. (2020). What May Characterise Teaching in Preschool? The Written Descriptions of Swedish Preschool Teachers and Managers in 2016. Scandinavian Journal of Educational Research, 64(1), 1–21. https://doi.org/10.1080/00313831.2018.1479301 Sudaryanti. (2015). Pentingnya Pendidikan Karakter bagi Anak Usia Dini. Jurnal Pendidikan Anak, 1(1). https://doi.org/10.21831/jpa.v1i1.2902